2018
DOI: 10.18203/2394-6040.ijcmph20180750
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice and learning needs of nursing personnel related to domestic violence against women: a facility based cross sectional survey

Abstract: Background: Domestic violence against women (DVAW) is widely recognized as a public health problem. In India, health sector response to DVAW is suboptimal. Present study aimed to assess the knowledge, attitude, practice and learning needs of nursing personnel regarding women’s health issues related to domestic violence.Methods: This facility based cross sectional study was carried out among 100 nursing personnel from Public sector in Delhi, selected using stratified random sampling. Data were collected using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…When considering age and years of experience, it is reasonable to think that professionals with maturity and expertise have a better understanding of IPV and greater skills to respond to victims/survivors of this type of violence [ 17 , 56 ]. Our indicia support these hypotheses, while there are studies that show contradictory results in this respect [ 58 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…When considering age and years of experience, it is reasonable to think that professionals with maturity and expertise have a better understanding of IPV and greater skills to respond to victims/survivors of this type of violence [ 17 , 56 ]. Our indicia support these hypotheses, while there are studies that show contradictory results in this respect [ 58 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 81%
“…Nurses have more and better opportunities to detect IPV, since they are the first healthcare providers and they spend more time with victims, as recognised by the International Council of Nurses [ 77 ]. However, although in every professional category a certain lack of training on the topic is detected [ 15 , 24 , 58 , 75 , 76 ], nurses generally believe that treating IPV is not part of their responsibilities [ 16 , 78 ], which may also be the opinion of those participating in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This puts them in a crucial position to address IPV from a facility-based perspective. IPV knowledge, attitude, and preparedness are important factors that affect nurses’ and midwives’ capacity to manage clients experiencing IPV [ 17 , 18 ] and are acquired through appropriate preservice and continuing education [ 19 ]. Therefore, evaluating nurses’ and midwives’ current conditions related to IPV knowledge, attitudes, and preparedness is important in determining their capacity to provide IPV care and services.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the participants’ background on IPV, the results showed that the participants were moderately prepared to respond to disclosure of abuse and had low scores in asking questions about IPV. Many studies found that health care providers, including physicians and nurses were not fully prepared to handle IPV cases [ 19 , 20 , 22 ], specifically in terms of male healthcare providers feeling uncomfortable asking sensitive questions to women [ 23 ]. Unfortunately, patients will be impacted by this, as many studies found that patients were afraid of being negatively judged and felt hesitant to express their experience of IPV to health care providers because of the latter’s inappropriate way of asking questions.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that nurses were not prepared to deal with IPV cases because they lacked the proper education and skills in identifying the symptoms and communicating with the victims [ 18 ]. Previous studies show that gender, educational level, work experience, and receiving preservice IPV training were associated with high scores in the knowledge of IPV [ 19 , 20 ]. With the uprising prevalence of IPV as a public health concern, nurses and physicians are recognized for their vital role in providing healthcare services for IPV.…”
Section: Introductionmentioning
confidence: 99%